Tofacitinib, an oral Janus kinase inhibitor, as monotherapy or with background methotrexate, in Japanese patients with rheumatoid arthritis: an open-label, long-term extension study. Issue 1 (December 2016) - Yamanaka, Hisashi; Tanaka, Yoshiya; Takeuchi, Tsutomu; Sugiyama, Naonobu; Yuasa, Hirotoshi; Toyoizumi, Shigeyuki; Morishima, Yosuke; Hirose, Tomohiro; Zwillich, Samuel
Abstract Background Tofacitinib is an oral Janus kinase inhibitor for the treatment of rheumatoid arthritis. Here, tofacitinib safety and efficacy data from a long-term extension study in Japanese patients are presented. Methods Study A3921041 was a multi-centre, open-label, long-term extension study that included Japanese patients who had participated in a prior Phase 2 or Phase 3 study of tofacitinib as monotherapy or with background methotrexate. Patients received tofacitinib 5 mg twice daily (BID) or tofacitinib 10 mg BID. Dose adjustment of tofacitinib during treatment period, and concomitant usage of disease-modifying antirheumatic drugs including methotrexate after week 12 were permitted. Primary endpoints were adverse events, laboratory parameters and vital signs. Secondary efficacy endpoints included American College of Rheumatology (ACR)20/50/70 response rates, Disease Activity Score (DAS)28-4(erythrocyte sedimentation rate (ESR))<2.6 response rate (DAS-defined remission) and Health Assessment Questionnaire-Disability Index (HAQ-DI) score. Safety and efficacy data were assessed throughout the study. Results A total of 486 patients were recruited and treated (1439.9 patient-years of exposure). 308 patients completed the study. Median (range) duration of treatment in this extension study was 1185 (5–2016) days. 476 patients (97.9 %) experienced adverse events; the majority of which (97.8 %) were of mild or moderate severity. The two most common treatment-emergent adverse events were nasopharyngitis (n = 293, 60.3 %) and herpes zoster (n = 94, 19.3 %). For all tofacitinib-treated patients, the incidence rate (patients with events per 100 patient-years) was 10.7 for serious adverse events, 3.3 for serious infections, 7.4 for herpes zoster (serious and non-serious) and 1.2 for malignancies (excluding non-melanoma skin cancer). Mean changes from baseline (start of the index study) in laboratory parameters were consistent with those seen in previously reported studies of tofacitinib. ACR20/50/70 response rates, DAS-defined remission rates and HAQ-DI scores were sustained through to study completion. Conclusions Tofacitinib (with or without background methotrexate) demonstrated a stable safety profile and sustained efficacy in Japanese patients with active rheumatoid arthritis. The risk of herpes zoster appears to be higher in Japanese patients treated with tofacitinib than in the global population. Trial registration Clinicaltrials.govNCT00661661 . Registered 7 February 2008.